Microcomputer engineering - Miller, Gene H. (Prentice Hall, 1993)
Presents the fundamentals of microcomputer hardware and software for those with little or no computer and electronics background, but with knowledge of digital systems. Using the Motorola 68HC11 as the example, the book covers both lecture and laboratory material.